Hubungan Interdialytic Weight Gain (IDWG) dengan Hipertensi Intradialisis pada Pasien yang Menjalani Hemodialisis - Yashinta Dewi; Theresia Tatik Pujiastuti; Avin Maria (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2022)
Background: Intradialytic hypertension is one of the problems experienced by patient with chronic kidney failure who undergoing hemodialysis with a prevalence of 13,2% to 33,9%. This kind of hypertension is one of the biggest causes of death in patient who undergoing dialysis, with a rate of 59%. Several factor can affect intradialytic hypertension, such as interdialytic weight gain, age, gender, and the duration of hemodialysis.Objective: To determine the characteristic of patients who underwent hemodialysis and to determine the correlation between interdialytic weight gain (IDWG) and confounding factors (age, gender, and the duration of hemodialysis) with intradialytic hypertension.Methods: This research used quantitative methods with observational analytic design. The sampling used simple random sampling with a sample size of 126 patients, who met inclusion and exclusion criteria. Data were collected using secondary data and then analyzed using Fischer Test.Results: The result showed there was no correlation between Interdialytic weight gain (IDWG) and intradialytic hypertension (p value = 0,484). For confounding variable, there was also no correlation between age with intradialytic hypertension (p value= 0,584), gender with intradialytic hypertension (p value= 1,000), and the duration of hemodialysis with intradialytic hypertension (p value= 0,333).Conclusion: There was no statistically significant correlation between interdialytic weight gain (IDWG) and intradialytic hypertension. Age, gender, and duration of hemodialysis did not contribute to intradialytic hypertension.ABSTRAKLatar belakang: Hipertensi intradialisis merupakan salah satu permasalahan yang dialami pasien gagal ginjal kronik yang menjalani hemodialisis, dengan prevalensi sekitar 13,2% sampai 33,9%. Kondisi ini menjadi salah satu penyebab kematian terbesar pada pasien yang menjalani dialisis, yaitu sebesar 59%. Beberapa faktor yang dapat memengaruhi hipertensi intradialisis, seperti Interdialytic Weight Gain, usia, jenis kelamin, dan lama hemodialisis.Tujuan: Mengetahui karakteristik pasien yang menjalani hemodialisis serta mengetahui hubungan antara Interdialytic Weight Gain (IDWG) dan faktor confounding (usia, jenis kelamin, dan lama hemodialisis) dengan hipertensi intradialisis.Metode: Penelitian ini menggunakan metode kuantitatif dengan desain analitik observasional. Jumlah sampel yang digunakan sebanyak 126 pasien, yang memenuhi kriteria inklusi dan eksklusi. Pengumpulan data menggunakan lembar dokumentasi subjek penelitian dan analisis data menggunakan Fischer test.Hasil: Hasil penelitian menunjukkan bahwa tidak ada hubungan antara Interdialytic Weight Gain (IDWG) dengan hipertensi intradialisis (p-value = 0,484). Pada faktor confounding juga tidak ada hubungan antara hipertensi intradialisis dengan usia (p-value= 0,584), dengan jenis kelamin  (p-value = 1,000), dan dengan lama hemodialisis (p-value= 0,333).Simpulan: Tidak ada hubungan antara Interdialytic Weight Gain (IDWG) dengan hipertensi intradialisis. Usia, jenis kelamin, dan lama hemodialisis, juga tidak berhubungan dengan hipertensi intradialisis.